Two New Methods of Supine Venographically Guided Popliteal Vein Puncture: A Retrospective Study. (October 2021) - He, Xinqi; Zhang, Lei; Qiu, Huiqing; Jiang, Xia; Zhang, Feng; Peng, Junlu; Zhang, Hongsong; Yu, Weifang; Gao, Xian; Dong, Ruitao; Zhao, Zengren
Abstract : Objective: Presently, the prone position is necessary for popliteal vein puncture access, but it makes the patients uncomfortable and does not allow traditional femoral or jugular access. To address these deficiencies, this study introduces two new methods, anterior and medial access carried out in the supine position. Methods: Venous interventions with punctures in the popliteal vein of 120 limbs in 97 patients were performed during the period from February 2017 to April 2019. After puncture, venographic guidance was achieved by dorsal vein injection of contrast medium. Interventional therapy was performed after puncture and insertion of the introducer sheath. Results: In all, 120 limbs were punctured in the popliteal vein, with technical success in 118 (98.3% in total) cases: 100%, 96.1%, and 100% successful punctures in, respectively, 32 anterior, 49 medial, and 37 posterior access cases. A comparison of the three groups revealed that the fluoroscopy time and duration of puncture were longer in the medial and anterior access groups than in the posterior access group. The rate of intra-operative and post-operative complications was 7.5% (9/120), with no statistically significant difference between the three access groups. Compared with the pre-operative median score of 2.5, the post-operative SVS (Society of Vascular Surgery) score of the popliteal vein was reduced to 1.5 in the anterior and 0.5 in the medial groups. Conclusion: Medial and anterior puncture of the popliteal vein in the supine position can be used as a safe alternative in venous endovascular therapy. The two new methods can mitigate frailty or respiratory problems resulting from the prone position and facilitate traditional femoral and jugular access.